2009
DOI: 10.1021/jo902493w
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular π−π Stacking Interactions in 2-Substituted N,N-Dibenzylaziridinium Ions and Their Regioselectivity in Nucleophilic Ring-Opening Reactions

Abstract: The ring opening of 2-substituted N,N-dibenzylaziridinium ions by bromide is known to occur exclusively at the substituted aziridine carbon atom via an S N 2 mechanism, whereas the opposite regioselectivity has been observed as the main pathway for ring opening by fluoride.Similarly, the hydride-induced ring opening of 2-substituted N,N-dibenzylaziridinium ions has been shown to take place solely at the less hindered position. In order to gain insight into the main factors causing this difference in regioselec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
50
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

8
0

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 62 publications
(104 reference statements)
3
50
0
Order By: Relevance
“…In the case of ATPH, the M06-2X hybrid functional [54,55] is a good choice to accurately quantify the adsorbate-ligand interactions and ligand-ligand interactions because it is used especially for medium range non-covalent interactions. In this functional, double Hartree−Fock exchange is included to improve the description of non-covalent interactions [56,57]. Furthermore, the double-zeta Pople basis set 6-311+g(d,p) was applied for subsequent energy refinements in case of ATPH.…”
Section: Cluster Calculationsmentioning
confidence: 99%
“…In the case of ATPH, the M06-2X hybrid functional [54,55] is a good choice to accurately quantify the adsorbate-ligand interactions and ligand-ligand interactions because it is used especially for medium range non-covalent interactions. In this functional, double Hartree−Fock exchange is included to improve the description of non-covalent interactions [56,57]. Furthermore, the double-zeta Pople basis set 6-311+g(d,p) was applied for subsequent energy refinements in case of ATPH.…”
Section: Cluster Calculationsmentioning
confidence: 99%
“…In contrast to their activated counterparts, non-activated aziridines have been evaluated to a limited extent up to now, both from a synthetic and a pharmacological point of view. Due to the presence of an electron-donating substituent at nitrogen, the latter aziridines have to be activated toward aziridinium ion intermediates prior to ring opening [18,19,20,21,22,23,24,25,26,27,28,29,30,31]. Within the present work, the scarcely studied subclass of non-activated 1-alkyl-2-(aminomethyl)aziridines [32,33,34,35,36,37,38,39] was employed as a source of substrates for the development of a novel entry toward the biologically relevant 1,2,3-triaminopropane unit through a highly regioselective and microwave-assisted ring opening by diethylamine in acetonitrile.…”
Section: Introductionmentioning
confidence: 99%
“…[44,48,[68][69][70][71][72][73][74][75][76][77] In an effort to account for dispersive interactions between the coke surface and aromatic rings of the radicals studied herein, the newly developed density functional M06-2X, shown to correctly predict p-p stacking interactions, was utilized. [68,70] Recent computational studies on aromatic dimers have shown that T-shaped and parallel-displaced configurations are nearly isoenergetic and are the most favorable among interactions between aromatic moieties. [78][79][80] In light of this, several types of stacking interactions between the coke models and the aromatic substituents of the radicals were taken into consideration.…”
mentioning
confidence: 99%
“…[26] p-p stacking in radical addition reactions with benzene: To probe the effect of stacking in radical reactions on coke surfaces, addition of representative aromatically substituted radical 2 on benzene was investigated. Stacked and nonstacked conformations of the addition transition states for radical 2 (2-add-stacked-TS and 2-add'-TS, respectively), optimized at the M06-2X/6-31 + GA C H T U N G T R E N N U N G (d,p) level of theory, used extensively in recent computational studies involving organic reactions with dispersive effects, [68,77,81] are depicted in Figure 2. A parallel-displaced conformation between the surface model benzene and one of the aromatic radical substituents (displaced 20.18 and 3.608 from center to center) can be seen in the case of 2-add-stacked-TS.…”
mentioning
confidence: 99%